2016
DOI: 10.1089/cyber.2015.0295
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Users' Discounting Behaviors Reflect an Inability to Delay Gratification, Not Risk Taking

Abstract: The relationship between impulse control disorder (ICD) behaviors and problematic Internet use (PIU) has been established in the literature. Our aim was to further investigate whether the ICDs of individuals suffering from PIU primarily involve an inability to delay gratification or a tendency to take risks. Using delay and probability discounting tasks, we compared the subjective value of discounting between PIU individuals and controls in conditions of gaining or losing different monetary amounts. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
3
17
2
Order By: Relevance
“…Together, these results suggest that individuals with IGD showed greater intertemporal and risky decisional impulsivity, which might serve as an etiological marker of addictive behaviors (Bickel, Koffarnus, Moody, & Wilson, 2014). Additionally, it should be noted that intertemporal and risky decision-making performance were only weakly associated with each other, supporting the viewpoint that intertemporal and risky decision-making are two relatively distinct components of decisional impulsivity and the idea that alterations on specific dimensions of decisional impulsivity may occur at different stages during the development of addiction (Li, et al, 2016;Reynolds, Karraker, Horn, & Richards, 2003;Reynolds, Richards, Horn, & Karraker, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…Together, these results suggest that individuals with IGD showed greater intertemporal and risky decisional impulsivity, which might serve as an etiological marker of addictive behaviors (Bickel, Koffarnus, Moody, & Wilson, 2014). Additionally, it should be noted that intertemporal and risky decision-making performance were only weakly associated with each other, supporting the viewpoint that intertemporal and risky decision-making are two relatively distinct components of decisional impulsivity and the idea that alterations on specific dimensions of decisional impulsivity may occur at different stages during the development of addiction (Li, et al, 2016;Reynolds, Karraker, Horn, & Richards, 2003;Reynolds, Richards, Horn, & Karraker, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…More surprisingly, PIU individuals in the present sample did not exhibit differences in impulse control in the face of reward stimuli. This finding is partially inconsistent with the literature, which has found differences in delay discounting in IGD and PIU individuals (Li et al, 2016;Tian, 2018;Wang et al, 2017). It is worth noting that the majority of these studies focused on gaming disorder, whereas the current study assessed PIU more broadly, not specific to gaming.…”
Section: Discussioncontrasting
confidence: 98%
“…One of these studies used an EEG gambling task, finding stronger SR in Internet-addicted youth (He, 2017). Two recent studies of IGD and one of PIU found enhanced SR and decreased ability to control impulsivity in the face of reward stimuli (Li et al, 2016;Tian, 2018;Wang et al, 2017). Other studies using self-report measures, however, have found a lack of association between risk taking and IGD/PIU (Ko et al, 2010;Sariyska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when faced with loss-related fairness decision-making, it may be difficult to affect individuals’ ideas and ways of thinking by humor; these individuals are likely to address the situation in a seemingly “stubborn” and serious way. Moreover, studies have found that gains and losses, as two independent contexts that are often unrelated, can be differentially affected by the same experimental manipulation (Li et al, 2016b). Besides the acceptance rates, we may use the indifference point as another sensitive index.…”
Section: Discussionmentioning
confidence: 99%
“…Human fairness decision-making behavior differs in gain and loss contexts. Although many studies have shown that equivalent value in decision-making is greater in loss contexts than that in gain contexts (Li et al, 2011, 2016a,b), few studies have investigated this issue in strategic situations. One study identified a difference in the UG for gains and losses and found that proposers would propose higher offers and the responders demand higher in loss context than those in gain context, suggesting that unfairness loom larger than unfairness in gain (Buchan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%